2010
DOI: 10.1007/s00044-010-9389-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of anti-inflammatory, analgesic, ulcerogenicity and nitric oxide-releasing studies of novel ibuprofen analogs as nonulcerogenic derivatives

Abstract: Since the last 41 years, Ibuprofen has been one of the most widely used Non-Steroidal Anti-Inflammatory Drug (NSAID) due to its anti-inflammatory actions. As all the NSAIDs are suffering from the deadlier GI toxicities, Ibuprofen also is no exception to these toxicities. The free -COOH group is thought to be responsible for the Gastrointestinal (GI) tract toxicity associated with all the traditional NSAIDs. Therefore, the main aim of this study was to develop new chemical entities as potential anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The analgesic activity was evaluated using the acetic acid induced writhing method using groups of six animals each. A solution of acetic acid (1% v/v) in distilled water was prepared and injected intraperitoneally in a volume of 0.1 mL.…”
Section: Methodsmentioning
confidence: 99%
“…The analgesic activity was evaluated using the acetic acid induced writhing method using groups of six animals each. A solution of acetic acid (1% v/v) in distilled water was prepared and injected intraperitoneally in a volume of 0.1 mL.…”
Section: Methodsmentioning
confidence: 99%
“…In the continuation of our previous work [11][12][13][14][15][16][17][18][19][20][21][22][23] , it was confirmed that until now none of the methods had used such a mild and green catalyst and solvents for Dakin oxidation. The designed method is suitable for the conversion of substituted benzaldehydes to its consequent substituted phenols.…”
Section: Introductionmentioning
confidence: 72%
“…2. Ethyl-2-(alkylsulphonyloxy) alkanoates (6)(7)(8)(9)(10) were prepared according to the published method [24] using ethyl 2-hydroxyalkanoates and mesyl chloride (MsCl) in dry dichloromethane. Reaction of these intermediates with a mixture of various alkylbenzenes and AlCl 3 yielded ethyl 2-(4-alkylphenyl)-2-alkylalkanoates (14-20) was examined.…”
Section: ▼ Chemistrymentioning
confidence: 99%